BANKING COMPETITION, CAPITAL ACCUMULATION, AND INTEREST ON RESERVES. - Ghossoub, Edgar A.; Reed, Robert R. (Economic Inquiry, 2021)
In recent years, the increased concentration of activity in the banking system has received much attention. In addition, numerous central banks have expanded their range of policy tools to include paying interest on reserves. The objective of this paper is to study the implications of concentration in the banking sector and the effects of various reserve policies. Changes in the competitive structure affect investment, risk‐sharing, and social welfare. In general, perfect competition should not be a regulatory goal for the banking system. Moreover, it is generally not optimal to pay the same interest rate on required reserves as excess reserves.